Existence of The Land Bank Agency in The Context of Investment Development in Indonesia - Raudhah, Putri; Kurniati, Nia (RechtIdee, 2024)
Land is an important component in the business world, so in its development it "forces" Indonesia to become an investment-friendly country. To achieve this, Indonesia created the Job Creation Law and formed the Land Bank to collect, manage and distribute land in Indonesia. However, there are pros and cons related to the substance contained in the Job Creation Law, such as seeming to revive the domain verklaring, the alleged bias of the Government regarding the granting of permits to business entities and/or investors, overlapping authority and misinterpretation of the public regarding the main duties and functions of the Land Bank which is considered a new forum for corruption,  collusion and nepotism (CCN) because, in the same sector, there is already the Ministry of ATR/BPN which also regulates the land sector in Indonesia, so that clear restrictions are needed between institutions, therefore this systematic review is a bridge for the Government, investors and the public to realize legal certainty.